The effects of substrate layer thickness on piezoelectric vibration energy harvesting with a bimorph type cantilever. (June 2018) - Palosaari, Jaakko; Leinonen, Mikko; Juuti, Jari; Jantunen, Heli
Graphical abstract: Highlights: Four piezoelectric bimorph type cantilevers for vibration energy harvesting were manufactured. The cantilevers had the same dimensions with different thicknesses of the steel substrate. Cantilevers were tuned to the same resonance frequency with different sizes of tip mass. Mechanical energy needed to harvest the same amount of electrical energy was compared between the cantilevers. The highest average power of 8.74 mW was recorded under 2.5 g-force at a resonance frequency. Abstract: In this research four piezoelectric bimorph type cantilevers for energy harvesting were manufactured, measured and analyzed to study the effects of substrate layer thickness on energy harvesting efficiency and durability under different accelerations. The cantilevers had the same dimensions of the piezoelectric ceramic components, but had different thicknesses of the steel substrate (no steel, 30 µm, 50 µm and 75 µm). The cantilevers were tuned to the same resonance frequency with different sizes of tip mass (2.13 g, 3.84 g, 4.17 g and 5.08 g). The energy harvester voltage outputs were then measured across an electrical load near to the resonance frequency (∼40 Hz) with sinusoidal vibrations under different accelerations. The stress exhibited by the four cantilevers was compared and analyzed and their durability was tested with accelerations up to 2.5 g-forces.